A Polymer-Binder-Free Approach to Creating Functional LiFePO4 Cathodes by Organic Ionic Plastic Crystal-Derived Ion-Conductive Binders - Daniela M. Josepetti; Maria Forsyth; Patrick C. Howlett; Hiroyuki Ueda (Batteries)
Lithium-ion batteries are a promising technology to promote the phase-out of fossil fuel vehicles. Increasing efforts are focused on improving their energy density and safety by replacing current materials with more efficient and safer alternatives. In this context, binary composites of organic ionic plastic crystals (OIPCs) and lithium salts show promise due to their impressive mechanical properties and ionic conductivity. Taking advantage of this, the present paper substitutes the commercial non-electrochemically active binder with an OIPC component, N-ethyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide ([C2mpyr][FSI]), in combination with LiFSI. Slurry-formulation experiments revealed that varying the new binder’s composition allows the production of diverse LiFePO4 (LFP) cathodes via the conventional fabrication process. Large amounts of OIPC−lithium salt mixtures in the composition yielded thick electrodes with expected nominal areal capacities of up to 3.74 mAh/cm2, where the balanced composition with a reduced Li+ concentration can demonstrate >1.5 mAh/cm2 at 0.1C. Lowering the amount of these ion-conductive binders enabled LFP cathodes to perform effectively under fast cycling conditions at a C-rate as high as 2C. Preliminary battery tests with a limited Li+ source demonstrated the feasibility of full-cell operation without using the lithium-metal anode. This work paves the way for developing advanced rechargeable batteries using OIPC-based ion-conductive binders for a wide range of applications.